Wing Dimorphism/polymorphism in True Bugs (Hemiptera, Heteroptera) From a Functional Viewpoint - a Review: Part II: Phytophagous Species - Gidó, Zsolt (Journal of Central European Green Innovation, 2023)
This is the second part of the article where the available information from the published literature on the wing dimorphism/polymorphism occurring among true bugs (Heteroptera) is reviewed from a functional viewpoint. This paper covers the case studies on phytophagous species and draws some general conclusions.  Wing dimorphism/polymorphism has been studied in detail at the red firebug: Pyrrhocoris apterus (Linnaeus, 1758), at some blissid species - mainly at the Oriental chinch bug: Cavelerius saccharivorus (Okajima,1922) - at some lygaeid species and at the red-shouldered soapberry bug Jadera haematoloma (Herrich-Schäffer, 1847) (Rhopalidae).  In general, the macropterous form has a delayed sexual maturation, which further enhances its dispersal ability but represents an obvious reproductive disadvantage. In most known cases of the hemipteran wing dimorphism/polymorphism the wing form is affected by environmental factors (polyphenism), but examples of genetically determined wing dimorphism also have been documented among Lygaeinae. Seasonal wing dimorphism/polymorphism is very common among the well-studied northern temperate species. Wing dimorphic/polymorphic phytophagous “outbreak” species (Blissidae, Leptoterna dolobrata) react with mass production of the otherwise rare macropters to high population density and altered food quality. An underlying wing muscle dimorphism/polymorphism frequently co-exists with the externally visible wing dimorphism/polymorphism. Known cases of full or partial de-alation are also mentioned and briefly discussed.
Keywords: wing dimorphism/polymorphism; Heteroptera; Pyrrhocoris apterus; Blissidae; Jadera haematoloma